THE EFFECTS OF RUPIAH CURRENCY, WORLD OIL PRICES, AND WORLD GOLD PRICE ON COMPOSITED STOCK PRICE INDEX (IHSG) IN 2016 - Bima Prawirosaputro; Yudith Dyah Hapsari (Jurnal Manajemen, 2017)
This study aims to determine and analyze the effects ofIndonesian Rupiah exchange rate, world oil prices, and world gold priceson IDX Composite in 2016. This research utilizedGeneralized Auto-Regressive Conditional Heteroscedasticity (GARCH) method on 234 daily observations throughout the whole year. This study results demonstrated that the Indonesian Rupiah exchange rate has a significant and negative impact, while the world gold and oil prices have a significant and positive impact on the IDX Composite in 2016. In addition to these results, the discovery and usage of GARCH method as the optimum econometric model found the variance of residuals of IDX Composite in 2016, which is also affected by the previous day residuals, but it is not affected by the variance of previous days residuals.